Physical science - Salibio, Mark B.; David, Oliver M. (Makati City : Diwa Learning Systems, Inc., 2019)
"Learning should always develop one' positive values. Through the strategically provided reflection activities in the modules, these values are ensured to strengthen your appreciation of the concepts of physical science as you apply them directly and indirectly to your personal life. The use of available and relevant online resources is also emphasized in the modules so that you will have a borderless horizon as you explore the current understanding of chemistry and physics. The learning experiences beyond the four walls of the classroom will give you the opportunity to learn and explore as much as you can take in at your own pace".
Includes bibliography.
English text.
Keywords: Physical sciences